William James, Mind-Cure, and the Religion of Healthy-Mindedness - Duclow, Donald F. (Journal of religion and health, 2002)
At the turn of the twentieth century, the mind-cure movement emphasized the healing power of positive emotions and beliefs. William James defended mind-cure during the Massachusetts legislature's debates on licensing physicians in 1894 and 1898. In The Varieties of Religious Experience (1902) he used the movement's therapeutic claims to illustrate the typically American, practical turn of the "religion of healthy-mindedness." Varieties sympathetically surveys mind-cure literature, but also criticizes healthy-minded religion for its limited range and refusal to confront tragedy and radical evil. Many of today's mind/body therapies continue the mind-cure tradition and retain the limitations that James noted.